ANALISIS PEMANFAATAN KAWASAN WISATA PANTAI BERBASIS KESESUAIAN LAHAN DAN DAYA DUKUNG LINGKUNGAN DI PANTAI KURI KABUPATEN MAROS PROVINSI SULAWESI SELATAN - Azis, Abdul; Kasnir, Muhammad; Asbar, Asbar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
Kuri Beach Tourism Nisombalia Village has great potential in attracting tourists, management and development. Management that does not pay attention to the carrying capacity aspect of the area causes environmental quality to decrease, this is the main attraction. This study aims to assess the land suitability and carrying capacity of Kuri Beach tourism in Nisombalia Village, Marusu District, Maros Regency, South Sulawesi. The research method employed land suitability and carrying capacity analysis through field observations and measurements of beach biophysical parameters. Results indicate that Kuri Beach has a suitability level of 71.25% for beach recreation activities (S2 category), 76.47% for relaxation activities (S2 category), and 79.48% for swimming activities (S2 category). The area's carrying capacity can accommodate 400 people per day for relaxation, 106 people for beach recreation, and 40 people for swimming. Tourist perceptions reveal that 90% consider the beach beautiful and 79.20% feel comfortable. The research recommends enhancing tourism promotion, developing tourist facilities, and limiting visitors during weekends to ensure area sustainability. The success of tourism development depends on government policy support and active community participation in preserving the beach environment.